An Atom Laser over Optical Lasers - Sah, Arbind Kumar (Himalayan Physics, 2013)
An atom laser is a coherent state of propagating atoms. They are created out of a Bose Einstein Condensation (BEC) of atoms which are output coupled using various techniques. An optical laser or conventional laser generates a coherent beam of light waves where as an atom laser produces a coherent beam of matter waves. An atom laser will have a major impact on the fields of atom optics, atom lithography and precision measurements. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 99-101 Uploaded date: 12/23/2013